Comparative Analysis of Proteome-Wide Lysine Acetylation in Juvenile and Adult Schistosoma japonicum - Li, Qing; Zhao, Nan; Liu, Mu; Shen, Haimo; Huang, Lin; Mo, Xiaojin; Xu, Bin; Zhang, Xumin; Hu, Wei (Frontiers in Microbiology, 2017)
Schistosomiasis is a devastating parasitic disease caused by tremotodes of the genus Schistosoma. Eggs produced by sexually mature schistosomes are the causative agents of for pathogenesis and transmission. Elucidating the molecular mechanism of schistosome development and sexual maturation would facilitate the prevention and control of schistosomiasis. Acetylation of lysine is a dynamic and reversible post-translational modification playing keys role in many biological processes including development in both eukaryotes and prokaryotes. To investigate the impacts of lysine acetylation on Schistosoma japonicum (S. japonicum) development and sexual maturation, we used immunoaffinity-based acetyllysine peptide enrichment combined with mass spectrometry, to perform the first comparative analysis of proteome-wide lysine acetylation in both female and male, juvenile (18 days post infection, 18 dpi) and adult (28 dpi) schistosome samples. In total, we identified 874 unique acetylated sites in 494 acetylated proteins. The four samples shared 47 acetylated sites and 46 proteins. More acetylated sites and proteins shared by both females and males were identified in 28 dpi adults (189 and 143 respectively) than in 18 dpi schistosomula (76 and 59 respectively). More stage-unique acetylated sites and proteins were also identified in 28 dpi adults (494 and 210 respectively) than in 18 dpi schistosomula (73 and 44 respectively). Functional annotation showed that in different developmental stages and genders, a number of proteins involving in muscle movement, glycometabolism, lipid metabolism, energy metabolism, environmental stress resistance, antioxidation, etc., displayed distinct acetylation profiles, which was in accordance with the changes of their biological functions during schistosome development, suggesting that lysine acetylation modification exerted important regulatory roles in schistosome development. Taken together, our data provided the first comparative global survey of lysine acetylation in juvenile and adult S. japonicum, which would deepen our understanding of the molecular mechanism of schistosome development and sexual maturation, and provide clues for the development of new anti-schistosome strategies.